Method for improving wear resistance of porcelain glazed brick by using artificial gemstone solid waste

By introducing cubic crystal phase zirconia and yttrium oxide in artificial gem solid waste into the glazed formula of porcelain glazed tiles, the high cost and many processes of the wear resistance of porcelain glazed tiles in the prior art are solved. The problem has achieved efficient and economical wear resistance.

CN119430654APending Publication Date: 2025-02-14GUANGXI MONALISA NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411742234.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the existing porcelain glazed tiles improve wear resistance, the cost is high and the process is many, and the effect of increasing wear resistance in the prior art is limited.

Method used

Introduce an appropriate amount of artificial gem solid waste, especially cubic crystal zirconium dioxide and yttrium oxide, to form efficient ceramic materials through combination with other raw materials and ball milling.

Benefits of technology

It significantly improves the wear resistance and glaze hardness of porcelain glazed tiles, enhances the toughness and wear resistance of brick surfaces, and reduces the cost of materials, solving the problem of disposal of artificial gem solid waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162827390000071
    Figure BDA0005162827390000071
Patent Text Reader

Abstract

The invention discloses a method for improving the wear resistance of a porcelain glazed brick by using artificial gemstone solid waste, and relates to the technical field of ceramic tile preparation. The invention relates to a method for improving the wear resistance of a porcelain glazed brick. The porcelain glazed brick is prepared from a glazed material containing artificial gem solid waste. The polishing glaze comprises the following raw materials in parts by weight: a parts of potassium feldspar (40 < = a < = 46), b parts of dolomite (10 < = b < = 13), c parts of washed soil (8 < = c < = 12), 8-10 parts of strontium carbonate, d parts of quartz (6 < = d < = 9), e parts of calcined talc (8 < = e < = 10), f parts of zinc oxide (4 < = f < = 6), g parts of aluminum oxide (1 < = g < = 3), 1-3 parts of wollastonite and h parts of artificial gemstone solid waste (2 < = h < = 5), and a + b + c + d + e + f + g = 89. According to the invention, the artificial gem solid waste is introduced into the formula of the polishing glaze, so that the pollution of the solid waste in the artificial gem industry can be reduced, the material cost of the polishing glaze is reduced, the wear resistance of the glazed brick can be improved, and a green and sustainable ecology is constructed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tile preparation, and in particular to a method for improving the wear resistance of porcelain glaze polished tiles by utilizing artificial gemstone solid waste. Background Art

[0002] Wuzhou is the world's largest artificial gem processing and trading center, with an annual output of more than 100 billion artificial gems, accounting for 80% of China's output and more than 70% of the world's output. It is known as the world's artificial gem capital. Cubic zirconia, commonly known as "zircon", is one of the most important raw materials for the production of artificial gems. Around 2022, Wuzhou will consume more than 4,600 tons of cubic zirconia in the production of semi-finished gemstones each year, generating a large amount of artificial gem solid waste. Solving the problem of artificial gem solid waste disposal is of great significance to the future sustainable development of the environment.

[0003] According to experience, the three minerals with the largest contents in artificial gemstone solid waste are: zirconium dioxide content is 75.20%, yttrium oxide content is 15.50%, and hafnium dioxide content is 1.68%. Zirconium dioxide has three crystal variants, namely monoclinic zirconium dioxide, tetragonal zirconium dioxide, and cubic zirconium dioxide. The monoclinic zirconium dioxide is stable at room temperature. As the temperature rises, at 850-1000℃, the crystal phase transforms into a tetragonal phase with better symmetry; at a higher temperature of 2370℃, it will transform into a cubic phase. If an appropriate amount of stabilizer yttrium oxide is added, at a temperature above 1500℃, the tetragonal zirconium dioxide will form a cubic zirconium dioxide solid solution together with the stabilizer, and no reversible crystal transformation will occur after cooling.

[0004] In the prior art, the patent "A high-performance wear-resistant glaze and its preparation method" application number: 201911144473.8 uses a wear-resistant glaze, and its raw materials are composed of 65-75% raw glaze powder and 25-35% frit powder by weight percentage; the raw glaze powder includes the following raw materials: 30-40% albite, 12-16% burned talc, 4%-10% kaolin, 10-15% calcite, 2-8% zinc oxide, 10-15% wollastonite, 10-20% corundum and 2-8% barium carbonate. The smoothness of the glazed tiles made with this glaze meets the requirements of the production process, and at the same time solves the contradiction between the transparency and wear resistance of the glaze layer. The wear resistance of the glazed tiles is greatly improved, the smoothness is high, and the color is good. However, the main component of corundum is aluminum oxide, which can increase the melting temperature and increase the high-temperature viscosity of the melt. Generally, the dosage cannot be too high. Excessive dosage will increase the hardness of the glaze while the transparency and color of the glaze will deteriorate. A large amount of co-solvent zinc oxide needs to be added, which will increase the preparation cost of the glazed tiles and is not conducive to mass production.

[0005] Patent "A wear-resistant glaze for improving the wear resistance of porcelain glazed tiles and its preparation method" application number: 202210066102.8 uses wear-resistant glazes made of potassium feldspar, talc, zinc oxide, quartz, calcite, corundum, kaolin, and calcined soil. The wear-resistant glaze for improving the wear resistance of porcelain glazed tiles can make the fully glazed finished product have stronger wear resistance. Corundum has the characteristics of high melting point, high hardness, and high specific gravity. It can strengthen the bonding between the body and glaze, and has the effect of improving the hardness and wear resistance of the glaze. Quartz, as the main component of the glass phase, can effectively increase the hardness of the glaze. Compared with the existing conventional production process, the present invention sprays a thin layer of wear-resistant glaze after the glaze pouring process. The silicon aluminum content is higher than that of the glaze, and a thin layer is covered on the surface of the glaze. After polishing, the hardness of the glaze can be directly improved. This will not only increase the production process by one more step and increase the workload, but also increase the wear resistance by a limited amount, and does not fundamentally achieve the effect of increasing the wear resistance of the glaze.

[0006] In summary, the applicant improves the wear resistance of glazed tiles by introducing an appropriate amount of artificial gemstone solid waste into the glaze formula. Summary of the invention

[0007] In view of the above shortcomings, the present invention provides a method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste. By introducing an appropriate amount of artificial gemstone solid waste into the glazing formula and using it to produce porcelain glazed tiles, the problem of high cost and multiple processes for improving the wear resistance of porcelain glazed tiles is solved. The specific technical scheme is as follows:

[0008] A method for improving the wear resistance of porcelain glaze tiles by using artificial gemstone solid waste, wherein the porcelain glaze tiles are prepared by using glaze containing artificial gemstone solid waste;

[0009] The glaze comprises the following raw materials in parts by weight: a part of potassium feldspar (40≤a≤46), b part of dolomite (10≤b≤13), c part of washed soil (8≤c≤12), 8-10 parts of strontium carbonate, d part of quartz (6≤d≤9), e part of calcined talc (8≤e≤10), f part of zinc oxide (4≤f≤6), g part of aluminum oxide (1≤g≤3), 1-3 parts of wollastonite and h part of artificial gemstone solid waste (2≤h≤5), wherein a+b+c+d+e+f+g=89.

[0010] Preferably, the glaze comprises the following raw materials in parts by weight: a part of potassium feldspar (44≤a≤46), b part of dolomite (12≤b≤13), c part of washed soil (9≤c≤11), 9-10 parts of strontium carbonate, d part of quartz (6≤d≤7), e part of talc (8≤e≤9), f part of zinc oxide (4≤f≤5), g part of aluminum oxide (2≤g≤3), 1-2 parts of wollastonite and h part of artificial gemstone solid waste (4≤h≤5), wherein a+b+c+d+e+f+g=89.

[0011] Preferably, the content of cubic zirconium dioxide in the artificial gemstone solid waste is more than 90%.

[0012] Preferably, the preparation method of the polishing glaze is: weigh each raw material by weight; mix the raw materials, add water, carboxymethyl cellulose and sodium tripolyphosphate and ball-mill together, and control the fineness of the balls to be 0.1-0.3wt% of the residue on a 325-mesh sieve to obtain a mixture; and age the mixture for 18-24 hours to obtain the polishing glaze.

[0013] Preferably, the raw materials are mixed, and 38 wt% of water, 0.13 wt% of carboxymethyl cellulose and 0.3 wt% of sodium tripolyphosphate are added and ball-milled together.

[0014] Preferably, the glaze coating method is: control the glaze specific gravity at 1.85-1.88, control the flow rate at 26-30s, use a bell jar to evenly pour the glaze on the brick, and then put it into the kiln for firing.

[0015] Preferably, the glaze specific gravity is controlled at 1.85-1.86, and the flow rate is controlled at 27-28s.

[0016] Preferably, the sintering temperature is 1140-1160° C., and the sintering time is 42 minutes.

[0017] The cubic zirconium dioxide in the artificial gemstone solid waste can maintain phase stability at different temperatures better than the monoclinic zirconium dioxide directly added to the glaze formula, thereby avoiding material cracking caused by changes in volume and shear stress caused by phase change, and improving the hardness, toughness and wear resistance of ceramic tiles. More than 90% of the zirconium dioxide in the artificial gemstone solid waste of the present invention belongs to the cubic phase, and the cubic zirconium dioxide has a greatly improved transparency in the glaze than ordinary monoclinic and tetragonal zirconium dioxide.

[0018] Yttrium oxide in artificial gemstone solid waste has good stability and bright color. It can be added to both the blank and the glaze. Adding an appropriate amount can refine the grains, increase the amount of liquid phase, fill the gaps between the grains, increase the density, increase the hardness, improve the toughness of the ceramic, enhance the wear resistance, and effectively eliminate bubbles, pinholes, microcracks and ripples formed in the ceramic during the sintering process.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention introduces an appropriate amount of artificial gemstone solid waste into the glaze formula. The cubic zirconium dioxide in the artificial gemstone solid waste (accounting for more than 90% of all crystal phases) can improve the wear resistance and glaze hardness of the glaze, thereby increasing the toughness, hardness and wear resistance of the brick surface. While ensuring good glaze performance, the wear resistance of the brick surface reaches level 4 2100 revolutions or above.

[0021] 2. The present invention introduces an appropriate amount of artificial gemstone solid waste into the glaze polishing formula. The yttrium oxide in the artificial gemstone solid waste can refine the grains, increase the liquid phase amount, fill the gaps between the grains, increase the density, increase the hardness, improve the toughness of the ceramic, enhance the wear resistance, and effectively eliminate the bubbles, pinholes, microcracks and ripples formed in the ceramic during the sintering process. At the same time, yttrium oxide acts as a stabilizer to improve the overall stability.

[0022] 3. The present invention adds an appropriate amount of aluminum oxide to the glaze formula to promote the refinement of zircon grains in artificial gemstone solid waste to obtain grains of uniform size. The interaction between the two helps to refine the grain structure and thus improve the overall performance of the ceramic.

[0023] 4. The present invention can improve the transparency of the glaze by controlling the glaze fineness to 0.1-0.3wt% of the residue passing through a 325-mesh sieve. The smaller the particle size of the material, the lower its melting temperature. Under the same firing conditions, more glass phases are produced, and the transparency of the glaze is improved accordingly.

[0024] 5. The present invention effectively solves the problem of disposal of artificial gemstone solid waste by adding an appropriate amount of artificial gemstone solid waste into the glaze, reduces the material cost of the glaze, improves the wear resistance of the glazed bricks, and provides a feasible direction for building green sustainable development. DETAILED DESCRIPTION

[0025] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0026] Example 1

[0027] The preparation process of porcelain glazed tiles: press molding → body drying → glaze application → inkjet pattern printing → drying → glaze application → firing → edge grinding → packaging.

[0028] The specific raw materials for the glaze polishing are as follows by weight:

[0029] 46 parts of potassium feldspar, 12 parts of dolomite, 10 parts of water-washed soil, 9 parts of strontium sulfate, 6 parts of quartz, 8 parts of burned talc, 4 parts of zinc oxide, 3 parts of aluminum oxide, 2 parts of wollastonite, and 2 parts of artificial gemstone solid waste.

[0030] Mix the glaze raw materials in proportion, put them into a ball mill, add 38wt% of water, 0.13wt% of carboxymethyl cellulose and 0.3wt% of sodium tripolyphosphate, control the fineness of the balls to be 0.1% (325 mesh sieve), age for 18h, control the specific gravity to be 1.85, control the flow rate to be 30s, use a bell jar to evenly pour the glaze on the brick, put them into the kiln for firing at a temperature of 1140℃ and a firing time of 42min, measure the wear resistance, Mohs hardness, glossiness, dirt absorption, and observe the glaze condition.

[0031] Example 2

[0032] The preparation process of porcelain glazed tiles: press molding → body drying → glaze application → inkjet pattern printing → drying → glaze application → firing → edge grinding → packaging.

[0033] The specific raw materials for the glaze polishing are as follows by weight:

[0034] 46 parts of potassium feldspar, 12 parts of dolomite, 10 parts of water-washed soil, 9 parts of strontium sulfate, 6 parts of quartz, 8 parts of burned talc, 4 parts of zinc oxide, 3 parts of aluminum oxide, 2 parts of wollastonite, 4 parts of artificial gemstone solid waste.

[0035] Mix the glaze raw materials in proportion, put them into a ball mill, add 38wt% of water, 0.13wt% of carboxymethyl cellulose and 0.3wt% of sodium tripolyphosphate, control the fineness of the balls to be 0.3% (325 mesh sieve), age for 24h, control the specific gravity to be 1.88, control the flow rate to be 26s, use a bell cover to evenly pour the glaze on the brick, put them into the kiln for firing at a temperature of 1160℃ and a firing time of 40min, measure the wear resistance, Mohs hardness, glossiness, dirt absorption, and observe the glaze condition.

[0036] Example 3

[0037] The preparation process of porcelain glazed tiles: press molding → body drying → glaze application → inkjet pattern printing → drying → glaze application → firing → edge grinding → packaging.

[0038] The specific raw materials for the glaze polishing are as follows by weight:

[0039] 46 parts of potassium feldspar, 12 parts of dolomite, 10 parts of water-washed soil, 9 parts of strontium sulfate, 6 parts of quartz, 8 parts of burned talc, 4 parts of zinc oxide, 3 parts of aluminum oxide, 2 parts of wollastonite, 5 parts of artificial gemstone solid waste.

[0040] Mix the glaze raw materials in proportion, put them into a ball mill, add 38wt% of water, 0.13wt% of carboxymethyl cellulose and 0.3wt% of sodium tripolyphosphate, control the fineness of the balls to 0.25% (325 mesh sieve), age for 20 hours, control the specific gravity to 1.87, control the flow rate to 28s, use a bell cover to evenly pour the glaze on the brick, put them into the kiln for firing at a temperature of 1150℃ and a firing time of 42min, measure the wear resistance, Mohs hardness, glossiness, dirt absorption, and observe the glaze condition.

[0041] Example 4

[0042] The preparation process of porcelain glazed tiles: press molding → body drying → glaze application → inkjet pattern printing → drying → glaze application → firing → edge grinding → packaging.

[0043] The specific raw materials for the glaze polishing are as follows by weight:

[0044] 41 parts of potassium feldspar, 12 parts of dolomite, 10 parts of water-washed soil, 10 parts of strontium sulfate, 9 parts of quartz, 10 parts of burned talc, 6 parts of zinc oxide, 1 part of aluminum oxide, 3 parts of wollastonite, 6 parts of artificial gemstone solid waste.

[0045] Mix the glaze raw materials in proportion, put them into a ball mill, add 38wt% of water, 0.13wt% of carboxymethyl cellulose and 0.3wt% of sodium tripolyphosphate, control the fineness of the balls to be 0.1% (325 mesh sieve), age for 24h, control the specific gravity to be 1.85, control the flow rate to be 26s, use a bell cover to evenly pour the glaze on the brick, put them into the kiln for firing at a temperature of 1140℃ and a firing time of 42min, measure the wear resistance, Mohs hardness, glossiness, dirt absorption, and observe the glaze condition.

[0046] Comparative Example 1

[0047] The amount of artificial gemstone solid waste in the glaze polishing is 6 parts, and the other raw materials and preparation method are the same as those in Example 3.

[0048] Comparative Example 2

[0049] The amount of alumina in the glaze is 5 parts, and other raw materials and preparation methods are the same as those in Example 3.

[0050] Comparative Example 3

[0051] The ball fineness is controlled at 0.5% (325 mesh sieve), and other raw materials and preparation methods are the same as those in Comparative Example 1.

[0052] The properties of the tiles prepared in the embodiment and the comparative example were tested respectively, and the results are shown in Table 1.

[0053] Comparative Example 4

[0054] 5 parts of zirconium silicate were added to the glaze to replace the artificial gemstone solid waste. Other raw materials and preparation methods were the same as those in Example 3.

[0055] Test method:

[0056] Antifouling performance: According to the antifouling performance determination method in GB / T3810.14-2016 Ceramic Tile Test Method.

[0057] Wear resistance and hardness: According to the wear resistance determination method of glazed tiles in GB / T3810.7-2016 Ceramic Tile Test Method.

[0058] Transparency: According to GB / T 3810.16-2016 Ceramic Tile Test Methods Part 16: Determination of Light Transmittance.

[0059] Table 1 Performance of each group of tiles

[0060]

[0061] It can be seen from the above test results that the wear resistance of the glazed tiles prepared in Examples 1-4 is improved, the anti-fouling performance is good, and the transparency is good, indicating that the ceramic tiles prepared by the method of the present invention have excellent performance. The glaze transparency of Comparative Example 1 deteriorates because the amount of artificial gem solid waste added increases (6 parts are added). With the increase of artificial solid gem solid waste, the content of zirconium oxide also increases. When zirconium oxide reaches a certain amount, it is easy to cause an opacifying effect and reduce the glaze transparency. It is necessary to improve the glaze transparency by reducing the particle size of the material. The smaller the particle size of the material, the lower its melting temperature. Under the same firing conditions, the more glass phases are produced, and the glaze transparency is improved accordingly. It can be seen from the test results of Comparative Examples 3 and 1 that when the proportion of artificial gem solid waste is too high, the effect of reducing the particle size of the material to improve the glaze transparency is limited, so the amount of artificial gem solid waste added is more suitable in the range of 2-5 parts.

[0062] From the test results of Comparative Example 2 and Example 3, it can be seen that adding an appropriate amount of aluminum oxide to the glaze formula can improve the overall performance of the porcelain tile. When the amount of aluminum oxide added is 5 parts, the glaze transparency and anti-fouling properties will deteriorate, so the amount of aluminum oxide added is controlled within 5 parts. From the test results of Comparative Example 4 and Example 3, it can be seen that adding conventional zirconium silicate (monoclinic phase zirconium dioxide) to the glaze formula will reduce the glaze transparency.

[0063] In summary, the present invention introduces an appropriate amount of artificial gemstone solid waste into the glaze formula, and the cubic phase zirconium dioxide in the artificial gemstone solid waste (accounting for more than 90% of all crystal phases) can improve the wear resistance of the glaze, and can increase the resistance to glaze cracking and glaze hardness, thereby increasing the toughness, hardness and wear resistance of the brick surface, while ensuring good glaze performance. The brick surface wear resistance reaches level 4 2100 turns and above. The present invention introduces an appropriate amount of artificial gemstone solid waste into the glaze formula, and the yttrium oxide in the artificial gemstone solid waste can refine the grains, increase the amount of liquid phase, fill the gaps between the grains, increase the density, increase the hardness, improve the toughness of the ceramic, enhance the wear resistance, and effectively eliminate the bubbles, pinholes, microcracks and ripples formed in the sintering process of the ceramic. At the same time, yttrium oxide acts as a stabilizer to improve the overall stability. The present invention adds an appropriate amount of aluminum oxide to the glaze formula to promote the refinement of zircon grains and obtain grains of uniform size. The interaction between the two helps to refine the grain structure, thereby improving the overall performance of the ceramic. The present invention can improve the transparency of the glaze surface by controlling the glaze fineness to 0.1-0.3wt% of the residue on the 325-mesh screen. The smaller the particle size of the material, the lower its melting temperature. Under the same firing conditions, the more glass phases are produced, and the transparency of the glaze surface is improved. The present invention effectively solves the problem of disposing of artificial gemstone solid waste by adding an appropriate amount of artificial gemstone solid waste to the glaze, reduces the material cost of the glaze, improves the wear resistance of the glaze brick, and provides a feasible direction for building green sustainable development.

[0064] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste, characterized in that: The porcelain glazed tile is prepared by using glaze containing artificial gemstone solid waste; The glaze comprises the following raw materials in parts by weight: a part of potassium feldspar (40≤a≤46), b part of dolomite (10≤b≤13), c part of washed soil (8≤c≤12), 8-10 parts of strontium carbonate, d part of quartz (6≤d≤9), e part of calcined talc (8≤e≤10), f part of zinc oxide (4≤f≤6), g part of aluminum oxide (1≤g≤3), 1-3 parts of wollastonite and h part of artificial gemstone solid waste (2≤h≤5), wherein a+b+c+d+e+f+g=89.

2. The method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 1, characterized in that: The glaze comprises the following raw materials in parts by weight: a part of potassium feldspar (44≤a≤46), b part of dolomite (12≤b≤13), c part of washed soil (9≤c≤11), 9-10 parts of strontium carbonate, d part of quartz (6≤d≤7), e part of calcined talc (8≤e≤9), f part of zinc oxide (4≤f≤5), g part of aluminum oxide (2≤g≤3), 1-2 parts of wollastonite and h part of artificial gemstone solid waste (4≤h≤5), wherein a+b+c+d+e+f+g=89.

3. A method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 1 or 2, characterized in that: The content of cubic zirconium dioxide in the artificial gemstone solid waste is more than 90%.

4. A method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 1 or 2, characterized in that: The preparation method of the polishing glaze is as follows: weighing each raw material by weight; mixing the raw materials, adding water, carboxymethyl cellulose and sodium tripolyphosphate and ball milling together, controlling the fineness of the balls to be 0.1-0.3wt% of the residue on a 325-mesh sieve to obtain a mixture; aging the mixture for 18-24h to obtain the polishing glaze.

5. The method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 4, characterized in that: The raw materials are mixed, and 38 wt % of water, 0.13 wt % of carboxymethyl cellulose and 0.3 wt % of sodium tripolyphosphate are added and ball-milled together.

6. The method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 4, characterized in that: The coating method of the polishing glaze is as follows: the specific gravity of the polishing glaze is controlled at 1.85-1.88, the flow rate is controlled at 26-30s, and the glaze is evenly poured on the brick blank using a bell jar, and then the brick blank is put into the kiln for firing.

7. The method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 6, characterized in that: The glaze specific gravity is controlled at 1.85-1.86, and the flow rate is controlled at 27-28s.

8. The method for improving the wear resistance of porcelain glazed tiles by using artificial gemstone solid waste according to claim 6, characterized in that: The sintering temperature is 1140-1160° C., and the sintering time is 42 minutes.

Citation Information

Patent Citations

  • High-performance wear-resistant glaze and preparation method thereof

    CN110683767A

  • Wear-resistant glaze for improving wear resistance of porcelain glazed brick and preparation method of wear-resistant glaze

    CN114315139A

  • Polished glaze, ceramic tile and preparation method

    CN112592061A

  • Super wear-resistant glazed brick glaze, preparation method thereof, glazed brick and preparation method thereof

    CN115385575A

  • Preparation method of artificial gem-containing solid waste zirconium material ultra-white cover glaze

    CN118993542A